The mast cells: the mastermind cells of the allergic inflammatory reaction - Piliponsky, Adrian (Henry Stewart Talks, 2020)
Mast cell morphology and their role in allergy and other inflammatory conditions, Mast cell precursors, tissue residency, and phenotypes, Mechanisms of mast cell activation and degranulation, Mast cell activating and inhibitory receptors, Mast cell mediator release